Cranioplasty - Ong, Adrian A.; Manning, James P.; Vincent, Aurora G.; Namin, Arya W.; Wang, Weitao; Ducic, Yadranko (Facial Plastic Surgery, 2021)
Calvarial defects are commonly encountered after neurosurgical procedures, trauma, and ablative procedures of advanced head neck cancers. The goals of cranioplasty are to provide a protective barrier for the intracranial contents, to restore form, and prevent syndrome of the trephined. Autologous and alloplastic techniques are available, each with their advantages and drawbacks. A multitude of materials are available for cranioplasty, and proper timing of reconstruction with attention to the overlying skin envelope is important in minimizing complications.
Keywords: cranioplasty; cranial reconstruction; pediatric cranioplasty; alloplastic; autologous